An outbreak of thyrotoxicosis in the city of Minas, Lavalleja country, Uruguay, July 2004 - Murillo, Nelly; Pereira, Mirian; Linder, Cristina; Vignolo, Julio; Belzanera, Cristina; Anchieri, Delvey; Hernandez, Silvia; Doll, Isabel; Alonso, Cristina; Méndez, Adriana (Revista de Salud Pública, 2014)
In the period from August 2003 to April 2004, an epidemic outbreak of thyrotoxicosis occurred in the city of Minas, Lavalleja county, Uruguay. The majority of cases affected residents of the ?España? quarter and its neighborhood. Symptoms, the thyroid scintigram and the laboratory analysis pointed to a diagnosis of silent thyroiditis, iodine ingestion, or thyroid hormones ingestion. A descriptive of 59 cases study was carried out. The evolution in time had the shape of a single-source epidemic curve, with both sexes equally affected. The etiologic hypothesis is the presence of thyroids or thyroid hormones in the meat consumed by the patients.